Joe the Hotel Boy; Or, Winning out by Pluck - Alger, Horatio, Jr., 1832-1899 (Salt Lake City, UT : Project Gutenberg, 2006)
"Joe the Hotel Boy; Or, Winning Out by Pluck" by Horatio Alger, Jr. is a novel written in the late 19th century that focuses on the themes of perseverance and resilience. The story follows a young boy named Joe Bodley, who faces various hardships and challenges as he strives to succeed in life, including working in different hotels and dealing with complex adult situations, all while maintaining his integrity. The opening of the novel introduces Joe during a storm with a wealthy friend, highlighting the disparity between their backgrounds. Joe is the grandson of a hermit, who he supports through hunting and fishing. As the narrative progresses, we learn about Joe's mysterious past, his sense of duty towards his uncle, and his dreams of discovering the truth about his family. The initial chapters set the stage for Joe's journey, filled with trials and adventures, establishing both the character$1 (Bs determination to rise above his circumstances and the various evildoers he will soon encounter. (This is an automatically generated summary.)s
Release date is 2006-03-18
Produced by Charles Keller and David Widger
Keywords: Swindlers and swindling -- Fiction; Conduct of life -- Fiction; Pennsylvania -- History -- 19th century -- Fiction; Hotels, motels, etc. -- Fiction